The presence of mallophaga species on wild partridge in the Elazi? district - Aksin, Nursel (My University, 2003)
The purpose of this study was to determine the presence of Mallophaga species on wild partridges in the Elazi? region. We inspected 68 partridges for Mallophaga species between November and January from 1996 to 2000. At least one species of Mallophaga was found on 48 partridges. Three species of Mallophaga were found on infested partridges. These species, were Goniodes dispar (Burmeister, 1838), Goniocotes pusillus (Nitzch in Giebel, 1866) and Menacanthus lyali (Rodriguez Caabeiro et al., 1983). These three Mallophaga species have not been reported before in Turkey.
Elazi? yöresi yabani kekliklerde bulunan mallophaga türleri
Keywords: G. dispar; G. pusillus; M. lyali; Mallophaga; Partridge; Turkey